Preparation and Evaluation of Smart Nanocarrier Systems for Drug Delivery Using Magnetic Nanoparticle and Avidin-Iminobiotin System. (28th August 2018) - Sun, Shuguo; Li, Beiping; Yang, Tao; Ma, Meihu; Lin, Qinlu; Zhao, Juanhong; Luo, Feijun
Abstract : Therapeutic efficacy and the regulation of drug release can be improved by using selective targeting drug delivery systems. In this paper, we have demonstrated avidin-immobilized magnetic nanoparticles (AMNPs) as a novel targeted drug delivery system to deliver iminobiotinylated daunomycin (IDAU). TEM, XRD, VSM, and FTIR were employed for the physicochemical characterization of the drug-loaded MNPs. The binding of IDAU had little effect on sizes of AMNPs (~35 nm), but the stability and dispersibility of the nanoparticles were improved. The study also found that the loading capacity and efficiency of nanoparticles were mainly dependent on affinity interaction between IDAU and AMNPs. The optimal loading capacity and efficiency of MNPs for IDAU were 0.408 ± 0.012 mg/g and 94.18 ± 2.64% according to the reversed-phase high-performance liquid chromatography (RP-HPLC) data, respectively. Under the conditions of pH 6.8 and 1 mmol/L of biotin, the drug-loaded MNPs released rapidly at beginning and then maintained at a certain controllable release level. The effect of IDAU on DLKP proliferation was tested, and the results showed that IC50 was (1.60 ± 0.05) × 10 −3  mg/mL. Our findings indicated that AMNPs hold tremendous potential as an effective drug delivery system.